2015
DOI: 10.1016/j.clim.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Control of intestinal homeostasis through crosstalk between natural killer T cells and the intestinal microbiota

Abstract: The human host and the intestinal microbiota co-exist in a mutually beneficial relationship, which contributes to host and microbial metabolism as well as maturation of the host’s immune system, among many other pathways (Tremaroli and Backhed, 2012; Hooper et al., 2012). At mucosal surfaces, and particularly in the intestine, the commensal microbiota provides ‘colonization resistance’ to invading pathogens and maintains homeostasis through microbial regulation of mucosal innate and adaptive immunity (Renz et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…However, we were unable to reproduce these findings, and our results showed that middle-aged and aged mice had slightly increased liver injury after α-Galcer injection with peak serum ALT levels of 500 IU/L compared to young mice. The reasons for this discrepancy are not clear, but it may be related to different environment and gut microbiota that are known to affect NKT cell development [34]. Moreover, the number and activation of hepatic NKT cells were comparable in ethanol-fed middle-aged and young mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, we were unable to reproduce these findings, and our results showed that middle-aged and aged mice had slightly increased liver injury after α-Galcer injection with peak serum ALT levels of 500 IU/L compared to young mice. The reasons for this discrepancy are not clear, but it may be related to different environment and gut microbiota that are known to affect NKT cell development [34]. Moreover, the number and activation of hepatic NKT cells were comparable in ethanol-fed middle-aged and young mice.…”
Section: Discussionmentioning
confidence: 99%
“…CD patients maintained in remission on 6-MP therapy had reduced numbers of colonic LP CD3 + CD56 + cells compared to individuals unexposed to 6-MP. Mucosal NKT cells are known to contribute to intestinal immune responses in health and disease although their precise role in inflammatory bowel disease is an ongoing area of research [48]. Stimulation of CD1d-restricted Type I NKT appeared to improve disease scores in murine model of DSS colitis [49].…”
Section: Discussionmentioning
confidence: 99%
“…High epithelial expression of Cd1d1 in intestine in response to microbial lipid antigens activates NKT-cells. 21 Recent evidence suggests that NKT-cells modulates host and commensal microbiota interactions, regulating intestinal homeostasis and preventing inflammation, 22 helping to explain similarities between NL, T1 and T2.…”
Section: Resultsmentioning
confidence: 99%